Organizational Decline: A Neglected Topic in Organizational Science1 - Whetten, David A. (Academy of Management Review, 1980)
Organizational decline has not been adequately examined by organizational scientists, because they are preoccupied with organizational growth and its consequences. The emphasis on growth reflects actual organizational conditions and the prevailing ideology in our society. However, predictions of an emerging era of retrenchment imply a need to study the management of organizational decline. In this paper, I propose an agenda of research, teaching, and consulting activities to rectify our neglect of this topic.